Sediment Dynamics Subject to Sea Level Rise in the Yangtze River Estuary - Chen, Wei; Ban, Haoyang; Mao, Chenhao; Liang, Huidi; Jiang, Mingtao (Journal of Ocean University of China, 2024)
In this study, a two-dimensional hydrodynamic and sediment transport model is established to quantify the influences of sea level rise on sediment transport in the Yangtze River Estuary (YRE). After validation, the model was employed to investigate the sediment transport and seabed evolution under four different scenarios of sea level rise, specifically, 0, 0.5, 1 and 1.5 m. The results reveal that there exists a ‘transition point (TP)’ of SSC in each main channel of YRE. Upstream of the transition point, the suspended sediment concentration (SSC) increases along with the rise in sea level, while downstream of the transition point, SSC decreases as sea level rises. Similarly, there are also transition points for topography evolution. The maximum scouring rate upstream of the transition points exceeds 4.32% for a 1.5 m rise in sea level, while the maximum deposition rate downstream of the transition points is 2.48%. The sediment fluxes from upstream to downstream in the branches of YRE are enhanced by the rise in sea level. The direction of sediment flux in the North Branch reverses downstream as sea level rises. The sediment flux from the North Channel towards downstream increases significantly, while there is no significant change in sediment flux for South Channel. Sediment deposition in the North Passage is also accelerated by sea level rise. In addition, the sediment flux from YRE to northern Jiangsu and Hangzhou Bay is also weakened by the rise in sea level.